2013
DOI: 10.1021/ar400066v
|View full text |Cite
|
Sign up to set email alerts
|

Designing Mimics of Membrane Active Proteins

Abstract: CONSPECTUS As a semi-permeable barrier that controls the flux of biomolecules in and out the cell, the plasma membrane is critical in cell function and survival. Many proteins interact with the plasma membrane and modulate its physiology. Within this large landscape of membrane-active molecules, researchers have focused significant attention on two specific classes of peptides, antimicrobial peptides (AMPs) and cell penetrating peptides (CPPs) because of their unique properties. In this account, we describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
152
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(154 citation statements)
references
References 74 publications
1
152
0
1
Order By: Relevance
“…This step is followed by the translocation of the Tat peptides that diffuse on the pore surface (Herce and Garcia, 2007). The pore formation model occurs through disruption of the lipid bilayer initiated by interactions between the side chains of basic amino acids such as Arg9 and phospholipid phosphate groups of cell membranes (Sgolastra et al, 2013). In this model, hydrophobic residues are near the lipid chains, and hydrophilic residues help in formation of the central pore.…”
Section: Translocation Of Cpps Into Cellsmentioning
confidence: 99%
“…This step is followed by the translocation of the Tat peptides that diffuse on the pore surface (Herce and Garcia, 2007). The pore formation model occurs through disruption of the lipid bilayer initiated by interactions between the side chains of basic amino acids such as Arg9 and phospholipid phosphate groups of cell membranes (Sgolastra et al, 2013). In this model, hydrophobic residues are near the lipid chains, and hydrophilic residues help in formation of the central pore.…”
Section: Translocation Of Cpps Into Cellsmentioning
confidence: 99%
“…The use of such naturally occurring AMPs for a rigorous study of relationship between the helical structure and antimicrobial activity is thus limited [76]. Recent studies, however, opened up the possibility of studying the helical structureactivity relationship more thoroughly through development of mimics of naturally occurring AMPs using both biotic and abiotic backbones [76][77][78][79][80][81]. Such oligomers, along with the ability to form a diverse range of proteomimetic structures, are also considerably less susceptible to proteolysis [77,82].…”
Section: Antimicrobial Agents With Peptide Backbonementioning
confidence: 99%
“…Structure-activity studies using such agents have not indicated any appreciable correlation between propensity for helix formation and antimicrobial activity [80]. The importance of other structural attributes such as amphiphilicity, charge-to-hydrophobic ratio, and oligomer size has been observed to be critical for such agents too [81,86,87]. Enhancement of hydrophobicity, generally resulting in greater stability of ordered helical conformations, has often been observed to adversely affect hemolytic activity of AMPs [82,85,87].…”
Section: Antimicrobial Agents With Peptide Backbonementioning
confidence: 99%
See 2 more Smart Citations